H-Mat hydrogen compatibility of polymers and elastomers. (31st March 2021) - Simmons, K.L.; Kuang, W.; Burton, S.D.; Arey, B.W.; Shin, Y.; Menon, N.C.; Smith, D.B.
Abstract: The H2@Scale program of the U.S. Department of Energy (DOE) Fuel Cell Technologies Office is supporting work on the hydrogen compatibility of polymers to improve the durability and reliability of materials for hydrogen infrastructure. The hydrogen compatibility program (H-Mat) seeks "to address the challenges of hydrogen degradation by elucidating the mechanisms of hydrogen-materials interactions with the goal of providing science-based strategies to design materials, (micro)structures, and morphology with improved resistance to hydrogen degradation." This research has observed interactions of hydrogen and pressure with model rubber-material compounds resulting in volume change and compression-set differences in the materials. The materials were investigated using helium-ion microscopy (HeIM), which revealed significant morphological changes in the plasticizer-incorporating compounds after exposure, as evidenced by time-of-flight secondary ion mass spectrometry. Additional studies using transmission electron microscopy and nuclear magnetic resonance were performed to correlate morphological change to potential chemical change in the materials. Highlights: Compression set in NBR shows a 40% increase after high-pressure hydrogen exposure Hydrogen-induced phase separation can cause a change in material performance The model NBR compound studied demonstrated a 72–85% increase in volume TEM shows an increasing number of particles in the polymer after hydrogen exposure